Delivery of Information on Gut Disease Using Visual Media Tools and Leaflets in The Village Karang Anyer Lubuk Pakam - Hayati, Kardina; Simarmata, Pratiwi Christa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
Health is the most important thing in carrying out daily life. Everyone wants to live a healthy life so they can live long. Health level is an indicator of life expectancy which is a reference in human development. The aim of this activity is to make people aware of gout in Karang Anyer Village, Lubuk Pakam. Degenerative diseases usually disrupt the human nervous system, blood vessels, muscles and bones, such as gout. Gout or gouty arthritis can attack the joints. PkM activities were carried out in Karang Anyer village where PkM participants were residents aged 26 years to over 65 years with a total of 30 participants. PkM participants consisted of 28 women and 2 men. The instruments used were visual media tools and leaflets. Then the increase in participants' knowledge of gout was measured using a questionnaire. The results of the activity were an increase in public awareness from 15% to 80% in the good category. The results of this activity show that community outreach has advantages in using visual media in providing public information. By using visual media, pictures are presented to make it easier for the public to understand the appeal messages, and the material presented is arranged in the form of brochures and distributed to the public. So that people can re-read the counseling material. Health education media in the form of pictures and brochures are considered effective and can be used in selecting public health education media.